Editors' Introduction - Susan Rothstein; Jurģis Šķilters (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
This volume contains a selection of the papers presented at the 11th International Symposium on Cognition, Logic and Communication which took place in Riga, at the University of Latvia on December 10-11 2015. The choice of topic reflected a growing understanding in the community of linguists and cognitive scientists that fundamental grammatical features of language, in particular the mass/count distinction, use of number words, and plurality, reflect our grasp of non-linguistic numerical operations, in particular individuation and measurement.